Soil Classification and Land Suitability for Agroforestry of Solo Hulu Watershed - Rahayu Rahayu (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2016)
Watershed requires management to diversify the function of sustainable biomass production, provide benefits for the socio-economic benefits and environmental aspects of land cover as a function of media production and water management regulator. It is known that upstream Solo watershed contributes sediment substantially to the silting of Gajah Mungkur reservoirs and carry sediment through Bengawan Solo river flow. Purpose of this study was to determine characteristics of soil and vegetation diversity in upstream Solo watershed area. Research was carried out by analysis of satellite observation and field survey with stratified random sampling method. Result showed that upstream Solo watershed is divided into six soil map units (SMU), soil was encountered into orders of Vertisols, Entisols, Alfisols and Inceptisols. Most areas of upstream Solo watershed was opened-vegetation with steep slope. Agroforestry type applied by public was simple agroforestry included mixed-cropping, barrier of bound and terrace and barrier of land ownership. Main vegetations were teak, mahogany and acacia. Land utilization was marginal with dry month length as an inhibitor factor.